Aggressive nasopharyngeal carcinoma presenting as diminution of vision: a case report - Ahmad, Kaleem; Ansari, Sajid; Dhungel, Kanchan; Gupta, Mukesh Kumar; Rauniyar, Raj Kumar; Siddiqui, Mohammad Azfar (Asian Journal of Medical Sciences, 2013)
Nasopharyngeal carcinoma is a malignant disease and is more common in males than in females with M:F ratio of 3:1. It has a bimodal peak at 16-20 and 46-50 years of age. Orbital involvement is seen in 3.2% and bilateral orbital invasion occurs in 0.7% of patients with nasopharyngeal carcinoma. Imaging has significant role in detecting the early nasopharyngeal carcinoma, tumor staging, involvement of lymph node, monitoring the patients after the therapy, to detect recurrence and radiation associated changes in the soft tissue and bone. We report a case of aggressive nasopharyngeal carcinoma in 22 years old male who presented with rapidly progressive diminution of vision. DOI: http://dx.doi.org/10.3126/ajms.v5i2.8297 Asian Journal of Medical Science, Volume-5(2) 2014: 130-133